PERAMALAN JUMLAH PASIEN DBD DI RSUD DR. SOESELO SLAWI DENGAN METODE DEKOMPOSISI DAN TRIPLE EXPONENTIAL SMOOTHING WINTER’S - Fitria, Jihan Dina; Karohmah, Nur; Sunarmi, Sunarmi (Universitas Muhammadiyah Semarang, 2017)
Forecast is forecasting what will happen to time to come, while plan is the determination of what will be done in time to come. The purpose of this research to know forecasting the number of dengue patients at RSUD Dr. Soeselo Slawi years 2016-2017 with the methods decomposition and triple exponential smoothing winter. Calculation done with compare in value smallest mape ( mean precentage absolute error) of decomposition obtained value mape of 40.94 while to a method of triple exponential smoothing winter produced model best with the level of accuracy of experiment α = 0,3; γ = 0,3; Δ = 0,3 obtained value mape namely 43,81, of both this method obtained the best method to forecasting the number of dengue patients at RSUD Dr.Soeselo Slawi Kabupaten Tegal that is a method of decomposition.The results of forecasting the number of dengue patients at RSUD Dr.Soeselo Slawi Kabupaten Tegal to 2016-2017 . Uses the method decomposition namely the period the first quarter of of 352, a period of the second quarter of 318, a periodof the third quarter of 211, the period from the fourth quarter of 226, the period form V quarter of 408 , the period from VI quarter of 366, the period from VII quarter of 242, the period from VIII quarter of 258. Keywords: Peramalan, DBD, Metode Dekomposisi, Metode Triple Exponential-Smoothing Winter’s,